Chromosome‐level genome and population genomic analysis provide insights into the evolution and environmental adaptation of Jinjiang oyster Crassostrea ariakensis. (9th December 2021) - Wu, Biao; Chen, Xi; Yu, Mengjun; Ren, Jianfeng; Hu, Jie; Shao, Changwei; Zhou, Liqing; Sun, Xiujun; Yu, Tao; Zheng, Yanxin; Wang, Yan; Wang, Zhenyuan; et al.
Abstract: The Jinjiang oyster Crassostrea ariakensis, naturally distributing in estuarine regions with low salinity, is an important economic and ecological species in China. However, studies on its genomics and population genetics remain lacking. Here, we assembled the chromosome‐level genome of a female C .  ariakensis and re‐sequenced 261 individuals from five locations in China representing three typical habitats. The C .  ariakensis genome was 662.9 Mb with contig N50 length of 5.9 Mb using PacBio HiFi‐CCS long reads, and 99.83% sequences were anchored onto 10 pseudochromosomes using Hi‐C data. A total of 26, 354 protein‐coding genes were predicted. We identified three significantly expanded gene families which are closely associated with osmotic pressure regulation, including CDO, SLC13 and SDR . Population structure analysis revealed that the C .  ariakensis from five locations were clustered into three typical groups (northern, southern and Shanghai) ( K  = 3) and their phylogenetic relationship was consistently correlated to their geographical distribution. Furtherly, the differentiation between northern and southern groups was clearly demonstrated by estimated population differentiation coefficient ( F ST  = 0.1154), and the PSMC distribution showed the two groups of effective population size separated at 0.1 Ma. Meanwhile gene flow from southern to Shanghai was detected. Selective sweep analysis between northern and southern group detected genes associated with heat response and salinity adaptation. This study could provide valuable genomic resources and information for further research on the molecular evolution, genetic breeding, biological function and evolutionary adaptation of C .  ariakensis .